On the prospects for the use of undenatured type II collagen in the treatment of osteoarthritis and other joint diseases - O. A. Gromova; I. Yu. Torshin; A. M. Lila; O. A. Shavlovskaya (Современная ревматология)
Standardized extracts of undenatured type II collagen (UC-II) are used as alternative approaches to the treatment of osteoarthritis (OA). The effect of UC-II extracts is associated with the modulation of the mechanisms of innate and acquired immunity, a decrease in the activity of proinflammatory cytokines and prostaglandins. Epitopes of native collagen in the structure of UC-II contribute to a decrease in the activity of autoimmune reactions that stimulate cartilage degradation. Interacting with discoidin receptors, UC-II accelerates the reconstruction of cartilage connective tissue and inhibits the pro-inflammatory effects of endogenous collagens. Experimental and clinical studies confirm the effectiveness of the use of standardized substances UC-II for acceleration of cartilage regeneration and reduce pain in OA and subclinical joint dysfunction.